Indexed journals with no or low article processing charges: An alternative publishing venue for Pakistani researchers - Aamir Raoof Memon; Ishtiaq Ahmed (Journal of the Pakistan Medical Association, 2024)
Publishing research is an integral part of an individual’s academic career. It is a requirement during higher education (e.g., Masters, PhD). Publication profile is also needed for job appointments and promotions as a mandatory requirement by several organisations. For example, the Higher Education Commission of Pakistan has specified the number of publications required for academic jobs and promotions.1 Therefore, many of us in academia are under constant pressure to publish for further professional growth. However, two major questions for the researchers from low- and middle-income countries, particularly Pakistan, are: 1) what are the options for openaccess publishing with no or low article processing charges? and 2) are such journals indexed in major bibliographic databases such as Scopus, Web of Science and/or PubMed? To answer these questions, this editorial aims to present information about indexed journals with low or no article processing charges, with particular emphasis on journals from Pakistan. Continued...